Несущие конструкции с повышеннными компоновочными характеристиками - Yefimenko, A. A.; Karlangach, A. P. (PE "Politekhperiodika", Book and Journal Publishers, 2016)
The authors propose solutions for constructing mechanical structures for electronic equipment in terms of plug-in units and subracks, allowing to increase the layout characteristics of electronic modules, sections and desktop devices and increase their functional capacity without changing the architecture of standard mechanical structures. The paper shows effectiveness of the developed solutions. There is a problem of restraining of mass redundancy of mechanical structures for electronic equipment in relation to the weight of the electronic components. On the other hand, the weight is an indicator of structural strength, providing of which is not less important problem.These problems can be solved in different ways, the main of which are the following: a) development of new mechanical structures for electronic equipment taking into account the development of the electronic components; b) improving layout characteristics of mechanical structures for electronic equipment without significant changes in their architecture.The aim of the study was to research mechanical structures of the first level (plug-in units and modules of the second level) of subracks to improve layout characteristics, and to develop methods for the use of connections for surface mounting and for the use of printed circuit boards of smaller dimensions without changing the architecture of the mechanical structures in order to improve layout characteristics.The research allowed the authors to develop the following solutions:1. The design of plug-in units in which instead of one printed circuit board (PCB) may be two, three or more PCBs of smaller dimensions to compensate a decrease in PCB fill factor in time and to increase the functional capacity of electronic modules.2. Construction of block designs with a bilateral arrangement of plug-in units and the organization of the electrical connections by way of backplanes with electrical connectors for surface mounting, which allows performing independent installation of plug-in units on both sides of the backplane and creates conditions for increasing the number of plug-in units.The proposed solutions do not lead to a change in the architecture of standard mechanical structures for electronic equipment or any performance degradation.